Study guides

☆☆

Q: What is the factorization of the trinomial below -x2 11x plus 26?

Write your answer...

Submit

Still have questions?

Related questions

(-4x + 3)(x - 2)Apex :)!!

It is: -4x^2 +11x -6 equals (-4x+3)(x-2) when factored

-(x + 13)(x - 2)

-x2 - 11x + 26= -x2 - 13x + 2x + 26= (2x - x2) + (26 - 13x)= x(2 - x) + 13(2 - x)= (2 - x)(x + 13)

Do you mean x2+11x-26 if so then it is (x-2)(x+13) when factored

It is (x+2)(x+9) when factored

(11x - 1)(11x - 1) (11x - 1)2

5x2+11x+2 = (5x+1)(x+2) when factored

Divide all terms by -1 so: x2-11x-26 = (x+2)(x-13) when factored

-x2 - 11x + 26 = -(x2 + 11x - 26) = -(x2 - 2x + 13x - 26) = -[ x(x - 2) + 13(x - 2) ] = -(x + 13)(x - 2) = (x + 13)(2 - x)

-x2 + 11x + 26 = -(x - 13)(x + 2) = (13 - x)(x + 2) = (x - 13)(-x - 2)

X2 -11x +10=(x - 1 )(x - 10)

People also asked